Evaluation of Nutritional Composition of Defatted Coconut Flour Incorporated Biscuits - Pathirana, H. P. D. T. Hewa; Lakdusinghe, W. M. K.; Yalegama, L. L. W. C.; Chandrapeli, C. A. T. D.; Madusanka, J. A .D. (International Coconut Community Journal, 2020)
Defatted coconut kernel is the major by-product of the dry method of virgin coconut oil (VCO) processing which includes high fiber content. It is ground into a fine powder, has a high potential to use as a composite matrix for baked food items with wheat flour. The aim of this research is to compare nutritional characteristics of defatted coconut flour incorporated biscuits (CF), desiccated coconut incorporated commercial biscuits (DC) and wheat flour-based commercial biscuits (WF) using white bread (WB) as a reference. Proximate composition (moisture, ash, crude fat, crude protein, crude fiber and carbohydrate), Hydrolysis Index (HI) and Predicted Glycemic Index (PGI) of samples were performed through standard in-vitro analysis methods. Results of the proximate analysis revealed that moisture (36.67±0.16 %) and protein (13.35±1.17 %) content of bread were significantly (p<0.05) higher while fat, fiber and ash content of CF incorporated biscuits were significantly (p<0.05) higher with the values of 26.67±1.87 %, 3.53±0.10 % and 4.70±2.61 % respectively. Free sugar glucose content (FSG) of WF was observed the highest significant (p<0.05) value of 5.88±1.03 % while the highest amount of rapidly available glucose (RAG) (81.45±5.27 %), slowly available glucose (SAG) (59.81±7.58 %), total glucose (TG) (99.16±5.56 %) were observed in reference food of bread. The PGI of three biscuit types belonging to the medium glycemic food with the values of 60.84, 64.53 and 62.90 respectively for CF, DC and WF treatments.